MicroRNA induction by copy number gain is associated with poor outcome in squamous cell carcinoma of the lung - Endi Xia (Nature Portfolio, 2018)
Abstract Copy number gains in cancer genomes have been shown to induce oncogene expression and promote carcinogenesis; however, their role in regulating oncogenic microRNAs (onco-miRNAs) remains largely unknown. Our aim was to identify onco-miRNAs induced by copy number gains in human squamous cell carcinoma (Sq) of the lung. We performed a genome-wide screen of onco-miRNAs from 245 Sqs using data sets from RNA-sequencing, comparative genomic hybridization, and the corresponding clinical information from The Cancer Genome Atlas. Among 1001 miRNAs expressed in the samples, 231 were correlated with copy number alternations, with only 11 of these being highly expressed in Sq compared to adenocarcinoma and normal tissues. Notably, miR-296-5p, miR-324-3p, and miR-3928-3p expression was significantly associated with poor prognosis. Multivariate analysis using the Cox proportional hazards model showed that miRNA expression and smoking were independent prognostic factors and were associated with poor prognosis. Furthermore, the three onco-miRNAs inhibited FAM46C to induce MYC expression, promoting proliferation of Sq cells. We found that copy number gains in Sq of the lung induce onco-miRNA expression that is associated with poor prognosis.